Adult age of vascular plant species along an elevational land‐use and climate gradient. Issue 10 (2nd April 2013) - Nobis, Michael P.; Schweingruber, Fritz H.
<x xml:space="preserve">Abstract</x> Trait variation across species plays a fundamental role in ecology and evolution, but quantitative analyses of key life‐history traits under natural conditions generally do not include a large number of species. In a comparative study, we analyzed interspecific variation in adult age as a minimum estimate of the lifespan of 708 vascular plant species along elevational gradients from 263–3175 m a.s.l. and compared this variation with predictions from r‐K selection theory and the metabolic theory of ecology (MTE). Age data based on annual ring counts of root collars and rhizomes were combined with a systematic sample of current species distributions in Switzerland (453 plots, each 1 km2). Elevation and temperature trends were investigated by regression analyses of the variation in adult age across species and species assemblages (median adult age) at the landscape level. We included climate, land use and geology as environmental predictors in multiple regressions and considered phylogeny by eigenvector filtering. We found a general increase in adult age towards higher elevations at the level of overall interspecific variation, and this trend was also detectable within individual plant families. Species generally had a shorter lifespan under warmer climates and, in agreement with r‐K prediction, in lowland agricultural landscapes. We found an exponential adult age–temperature relationship that is consistent with MTE. The estimate of the MTE parameter 'activation energy' for median adult age in multiple regression was 0.65 eV (95% CI 0.62–0.69 eV) which coincided with the predicted range of 0.60–0.70 eV. Our results imply that climate warming could accelerate species turnover rates by favoring short‐lived species over the whole range of life histories and species assemblages. Besides the strong temperature relationship, residual variability and confounding factors demonstrate the need for additional research about interactions between broad‐scale constraints and more local drivers of life‐history variation.